The Role of Indigenous Peoples in Natural Resource Management Based on the Dimensions of Legal Philosophy - Aulasysyifa Sholihah; Sri Wahyu Handayani; Tedi Sudrajat (CV Edujavare Publishing, 2026)
Indigenous customary law communities play a strategic role in natural resource management through customary law and local wisdom oriented toward environmental sustainability. However, natural resource management in Indonesia still faces various challenges, including excessive exploitation, weak recognition of customary rights, and inadequate legal protection for indigenous communities. This study aims to analyze the role of indigenous customary law communities in natural resource management and the legal protection of their rights from a legal philosophy perspective. The research employs normative legal research using statutory and conceptual approaches. Primary, secondary, and tertiary legal materials were analyzed qualitatively. The results show that indigenous communities contribute significantly to environmental conservation through customary norms, local wisdom-based management systems, and social monitoring mechanisms that promote balance between human interests and environmental sustainability. From a legal philosophy perspective, these practices reflect justice, utility, and sustainability. Legal protection is constitutionally recognized under Article 18B paragraph (2) and Article 28I paragraph (3) of the 1945 Constitution. However, implementation remains constrained by conditional recognition, uncertainty over customary rights, and conflicts over natural resource control. Therefore, stronger legal policies are needed to ensure certainty, effective recognition, and equitable protection.